Kesadaran Siswa Mengimplementasikan Kedisiplinan di MAN 2 Bukittinggi - Luthvita Crishanti Sausan; Fadilla Yusri; Hendri Efendi (Pusat Riset dan Inovasi Nasional, 2024)
In implementing student discipline at MAN 2 Bukittinggi, it is related to the condition of disciplinary attitudes among MAN 2 Bukittinggi students, knowing the process and character of student discipline, which focuses on organizing activities and models of daily routine habits obtained through the guidance process carried out. out so that it can describe the discipline of MAN students. 2 Bukittinggi, good at discipline, discipline in obeying the rules that apply at school. Although there are still many who do not obey the existing regulations that apply at school. Through the application of student discipline, it is useful in establishing school regulations and familiarizing students with school regulations. Evaluations that can be carried out by schools look at the extent of success in implementing statutory regulations and the obstacles experienced, including the lack of awareness of students in implementing the discipline that applies at school. From this, student awareness greatly influences the rules and regulations of the MAN 2 Bukittinggi school.